2015
DOI: 10.1155/2015/517359
|View full text |Cite
|
Sign up to set email alerts
|

Post-Transplant Lymphoproliferative Disorder in Liver Transplant Recipients: Characteristics, Management and Outcome from a Single-Centre Experience with >1000 Liver Transplantations

Abstract: This series from a single large-volume centre showed excellent short and long-term survival after PTLD in adult LTRs who were EBV negative, had early disease and showed complete response. Consistent with the known in vitro antiproliferative effect of sirolimus, switching IS from calcineurin inhibitor to sirolimus may improve survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 32 publications
4
40
1
3
Order By: Relevance
“…We report a predominance of extranodal manifestations in our cohort, consistent with previous published literature: 8,35,36 we found that GI manifestations, in particular, appeared to be much more prevalent than in Western studies-81.3% (13/16) of diagnosed PTLD cases had some form of GI involvement, compared to previously published estimates at 10%-29%. 37,38 The prevalence of GI PTLD in other small…”
Section: Clinicopathological Spectrumsupporting
confidence: 92%
“…We report a predominance of extranodal manifestations in our cohort, consistent with previous published literature: 8,35,36 we found that GI manifestations, in particular, appeared to be much more prevalent than in Western studies-81.3% (13/16) of diagnosed PTLD cases had some form of GI involvement, compared to previously published estimates at 10%-29%. 37,38 The prevalence of GI PTLD in other small…”
Section: Clinicopathological Spectrumsupporting
confidence: 92%
“…Risk factors for PTLD after liver transplant include EBV seronegativity, early age (especially children and adolescents), and high doses of immunosuppression and first year after transplant (11)(12)(13). In our case, 50% of recipients had EBV seronegativity prior to the liver transplant.…”
Section: Risk Factors For Ptld Developmentmentioning
confidence: 63%
“…6,22,23 Although previously it has been reported that the majority of PTLD cases occur early posttransplant, within the first 1-2 years, more recent data suggest that late-onset PTLD is more common. 6,24 This is in keeping with our data in which 71% of cases occurred beyond 24 months. However, in contrast to other series in which PTLD occurring early is usually EBV positive, our series shows a similar distribution of EBV-positive PTLD in the early and late groups with the caveat that there are missing data.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we did not identify any impact of several clinical variables on response rates or OS including age, stage, early or late PTLD, EBV status and graft involvement. 6,24,26 This is possibly due to sample size. We included one patient in this study who was treated with single-agent rituximab for EBV reactivation alone with no clinical evidence of PTLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation